Sequence Analysis of Malaysian Infectious Bursal Disease Virus Isolate and the Use of Reverse Transcriptase Nested Polymerase Chain Reaction Enzyme-Linked Immunosorbent Assay for the Detection of VP2 Hypervariable Region - Phong, S. F.; Hair-Bejo, M.; Omar, A. R.; Aini, I. (American Association of Avian Pathologists (AAAP), 2003)
The VP2 hypervariable region of P97/302 local infectious bursal disease virus (IBDV) isolate was amplified by the reverse transcriptase (RT) nested polymerase chain reaction (PCR) and cloned. This region of P97/302 local isolate was sequenced and compared with eight other reported IBDV sequences. The result showed that P97/302 IBDV was most identical to the reported very virulent IBDV strains because it has amino acid substitutions at positions 222, 256, 294, and 299, which encode alanine, isoleucine, isoleucine, and serine, respectively. This region can be digested with restriction enzymes of Taq1, Sty1, Ssp1 but not with Sac1. The P97/302 isolate was then used for the optimization of RT nested PCR enzyme-linked immunosorbent assay (ELISA). The RT nested PCR ELISA was able to detect 10-4 dilution of the infected bursa homogenates and was 10 times more sensitive when compared with the agarose gel detection method. The RT nested PCR ELISA can detect up to 0.48 ng of the PCR product. The specificity of this nested PCR ELISA was also high (100%).